Study on the Socio-Economic Condition of Fishermen of the Punorvaba River under Sadar Upazila, Dinajpur - Hossain, Faishal Ibna; Miah, Md. Idris; Pervin, Rubaiya; Hosen, Md. Hafiz All; Haque, Md. Rezoanul (Journal of Fisheries, 2015)
The present study was conducted to evaluate livelihood status of fishing community of the Punorvaba River under Dinajpur Sadar Upazila during the period from January to August, 2013. The livelihood status of fishermen were studied in terms of age structure, family size and type, occupation status, educational status, housing condition, drinking water facilities, sanitary facilities, health facilities, credit facilities and monthly income. It was found that most of the fishermen were belonged to the age groups of 36-45 years (40%), represented by 90% Muslim. The family size of fishing community is usually consisted of 5-7 members. Over 45% of the fishermen primarily engaged in fishing. Among them 50% was illiterate and 7% was SSC and above group. About 40% of the fishermen received health service from village doctors, 23% from upazila health complex and remaining 7% got health service from MBBS doctors. Some management strategies such as prohibition of catching brood fish, control of destructive gears, establishments of fish sanctuaries, release of fish fry have been suggested by the fishermen to stop the decreasing trend in the fish catch and to enhance fish production.